Enhancement of critical heat flux and superheat through controlled wettability of cuprous-oxide fractal-like nanotextured surfaces in pool boiling. (April 2017) - Jo, Hong Seok; An, Seongpil; Park, Hyun Goo; Kim, Min-Woo; Al-Deyab, Salem S.; James, Scott C.; Choi, Jeehoon; Yoon, Sam S.
Highlights: Highly nanotextured "fractal-like" nanostructures on nickel-chrome wires improved the pool boiling performance. Vapor bubbles from wire Joule heating formed, whose buoyant rise removed heat and promoted cooling. Hydrophobic texturing is desirable for electronics cooling, which demands low surface temperatures. Fractal-like hydrophilic surfaces increased the number of nucleation sites and the critical heat flux. Abstract: Highly nanotextured surfaces fabricated by electroplating are demonstrated in pool-boiling applications. Nickel-chrome wires were electroplated with copper and then annealed to cuprous oxide before being subject to Joule heating in a water bath. Vapor bubbles formed whose buoyant rise removed heat and promoted cooling. Hydrophobic and hydrophilic nanotextured surfaces could be tuned by varying the electroplating time. A hydrophobic surface enhanced bubble dynamics to locally decrease the surface temperature of the wire, which, in turn, enhanced superheat and the effective heat transfer coefficient. Conversely, a hydrophilic surface, characterized by a "fractal-like" surface decorated with numerous nucleation sites, increased the overall heat removal and thus the critical heat flux. These nanotextured surfaces were characterized by scanning electron microscopy and their pool boiling dynamics were visualized with a high-speed CCD camera. Theoretical heat-transfer estimates compared well with experimental data.